Inside spin the dark underbelly of the PR industry - Burton, Bob. (Crows Nest Allen & Unwin, 2007)
Corporate and government spin doctors invisibly influence just about every news story we read, see and hear. Perhaps even more significant is what they manage to keep out of the news altogether. Bob Burton peers inside the hidden world of corporate and government spin to reveal the extraordinary impact of the PR industry. He illuminates the hardball and soft tactics used by PR companies to smother dissenting viewpoints, mask sponsors, attack corporate competitors and influence politicians. Through a series of detailed case studies from both private and public sectors, he shows just how much PR controls what we see, hear and think about the organisations that manage our society.
Includes bibliographical references (p. 267-299) and index.
Keywords: Public relations